Pemikiran pendidikan Syed M. Naquib al-Attas dalam Buku "The Concept of Education in Islam" - Hamka, Syamsuar; Umarella, Samad (Tawazun: Jurnal Pendidikan Islam, 2024)
Al-Attas is a prominent individual whose concepts continue to spark discussions and used as a reference in highlighting Islam as a world view in the modern era. In general, what underlies al-Attas's thinking is to summarize Muslims in various systems of life, especially in the fields of education and scientific development. As a result, al-Attas' works generally focus on restoring Islamic values as a worldview, encouraging Islamic independence from the slavery of Western civilization, and the concept of desecularization, an effort to integrate science. Therefore, al-Attas proposed several reform concepts in The Concept of Education in Islam, including the Islamization of science, namely the process of deconstructing Western human knowledge and reconstructing it into an Islamic knowledge system, as well as the concept of Islamic education which aims to create perfection. namely humans who are aware of their individuality and technical skills. The type of research used in this research is library research (penelitian kepustakaan) with the aim of finding out Naquib Al-Attas' thoughts on the concept of education in Islam. Abstrak Al-Attas merupakan salah satu tokoh yang gagasannya masih diperdebatkan dan dijadikan acuan dalam menyoroti Islam sebagai pandangan dunia di era modern. Secara umum, yang mendasari pemikiran al-Attas adalah kemunduran umat Islam dalam berbagai sistem kehidupan, khususnya dalam bidang pendidikan dan pengembangan ilmu pengetahuan. Alhasil, karya-karya al-Attas secara umum fokus pada pemulihan nilai-nilai Islam sebagai pandangan dunia, mendorong kemandirian Islam dari perbudakan peradaban Barat, dan konsep desekularisasi, upaya mengintegrasikan ilmu pengetahuan. Oleh karena itu, al-Attas mengajukan beberapa konsep pembaharuan dalam The Concept Of Education In Islam, antara lain Islamisasi ilmu pengetahuan, yaitu proses dekonstruksi ilmu pengetahuan Barat dan merekonstruksinya menjadi sistem pengetahuan Islam, serta konsep pendidikan Islam yang bertujuan untuk menciptakan manusia sempurna. yaitu manusia yang sadar akan individualitas dan keterampilan teknisnya. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian kepustakaan (library research), dengan tujuan untuk mengetahui pemikiran Naquib Al-Attas Dalam The Concept Of Education In Islam.